Degradation of Proof of Certificate of Title through Complete Systematic Land Registration in Civil Disputes - Rudi Mulyanto; Marwiyah; Etis Cahyaning Putri (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
The Certificate of Ownership of the Complete Systematic Land Registration serves as an important means of proof in ensuring legal certainty of land rights. However, in civil disputes, the evidentiary strength can be weakened if the certificate issuance process is not supported by legal grounds, physical data, juridical data, and accurate verification. This study aims to analyze the degradation of the proof of Certificate of Property Rights through Complete Systematic Land Registration in civil disputes. The research uses a document-based empirical juridical method with a case study approach to Decision Number 221/Pdt.G/2024/PN Byw. Data was collected through literature studies and documentation of court decisions, land regulations, land registration documents, and related legal literature. The analysis was carried out using qualitative content analysis and legal arguments through codification of the basis of rights, physical data, juridical data, systematic land registration procedures, and judges' considerations. The results of the study showed that the degradation of evidence occurred due to data inconsistency with the village administration, weak research on the basis of rights, conflict of interest in the verification process, and lack of optimal institutional control before the certificate was issued. A certificate of title is not seen as absolute evidence, but rather a strong piece of evidence that can be broken by more convincing evidence of inheritance, land history, and possession facts. This study emphasizes the importance of independent verification, land data validation, and strengthening the accountability of Complete Systematic Land Registration to prevent disputes and increase the evidentiary strength of certificates.